A month for the mission: using a sentinel approach to determine the transmission window of digenean cercariae in the subarctic White Sea. (25th August 2021) - Nikolaev, Kirill E.; Levakin, Ivan A.; Galaktionov, Kirill V.
Abstract: In the digenean life cycle the cercaria ensures an important transmission stage, from the first intermediate host to the second or the definitive host. In regions with pronounced seasonality, this process occurs within a certain interval, the transmission window. In high latitudes, the size of transmission window has previously been determined only by comparing data on seasonal dynamics of infection level in various categories of hosts or extrapolating the results of laboratory experiments on cercarial biology to natural conditions. In this study, we evaluated the dynamics of infection of the second intermediate hosts (mussels Mytilus edulis ) with cercariae of two digenean species, Himasthla elongata (Himasthlidae) and Cercaria parvicaudata (Renicolidae), at a littoral site at the White Sea by exposing cages with uninfected mussels during the warm season. This is the first such study in a subarctic sea. Mussel infection was observed from May to mid-September, but its intensity was the greatest only for approximately a month, from some moment after 10 July to mid-August, when water temperature was within the optimal range for cercarial emergence in both studied species (15‒20°C). During this time, the mussels accumulated 66.3 ± 6.2% metacercariae of H . elongata and 79.7 ± 5.3% metacercariae of C . parvicaudata out of the total number accumulated during the experimental period. We suggest that climate warming at high latitudes may prolong the period when the water temperatures are optimal for cercariae emergence, thereby intensifying digenean transmission in coastal ecosystems.